Deep Insights Into the Plastome Evolution and Phylogenetic Relationships of the Tribe Urticeae (Family Urticaceae) - Ogoma, Catherine A.; Liu, Jie; Stull, Gregory W.; Wambulwa, Moses C.; Oyebanji, Oyetola; Milne, Richard I.; Monro, Alexandre K.; Zhao, Ying; Li, De-Zhu; Wu, Zeng-Yuan (Frontiers in Plant Science, 2022)
Urticeae s.l, a tribe of Urticaceae well-known for their stinging trichomes, consists of more than 10 genera and approximately 220 species. Relationships within this tribe remain poorly known due to the limited molecular and taxonomic sampling of previous studies, and chloroplast genome (CP genome/plastome) evolution is still largely unaddressed. To address these concerns, we used genome skimming data—CP genome and whole nuclear DNA (18S-ITS1-5.8S-ITS2-26S); 106 accessions—for the very first time to attempt resolving the recalcitrant relationships and to explore chloroplast structural evolution across the group. Furthermore, we assembled a taxon rich two-locus dataset of trnL-F spacer and nuclear ITS (nrITS) sequences across 291 accessions to complement our genome skimming dataset. We found that Urticeae plastomes exhibit the tetrad structure typical of angiosperms, with sizes ranging from 145 to 161 kb and encoding a set of 110 to 112 unique genes. The studied plastomes have also undergone several structural variations, including inverted repeat (IR) expansions and contractions, inversion of the trnN-GUU gene, losses of the rps19 gene, and the rpl2 intron, and the proliferation of multiple repeat types; 11 hypervariable regions were also identified. Our phylogenomic analyses largely resolved major relationships across tribe Urticeae, supporting the monophyly of the tribe and most of its genera except for Laportea, Urera, and Urtica, which were recovered as polyphyletic with strong support. Our analyses also resolved with strong support several previously contentious branches: (1) Girardinia as a sister to the Dendrocnide-Discocnide-Laportea-Nanocnide-Zhengyia-Urtica-Hesperocnide clade and (2) Poikilospermum as sister to the recently transcribed Urera sensu stricto. Analyses of the taxon-rich, two-locus dataset showed lower support but was largely congruent with results from the CP genome and whole nuclear DNA dataset. Collectively, our study highlights the power of genome skimming data to ameliorate phylogenetic resolution and provides new insights into phylogenetic relationships and chloroplast structural evolution in Urticeae.